Pengaruh Pola Asuh Dan Pola Bermain Terhadap Kemampuan Komunikasi Sosial Pada Anak Autism Di Surakarta - Sudarman Sudarman; Roy Romey Daulas M (Poltekkes Kemenkes Surakarta, 2019)
Background: Family is the most important role in a child's life, a place where he learns and expresses himself as a social creature, because the family provides the basis for the formation of personality, character, morals, socio-cultural and religious development as the first and foremost education place for children. The character development, morals and social development is very much influenced by parenting style and the playing pattern of child. Objective,to find out whether there is an influence of parenting style and playing patterns towards the ability of Social Communication in Children with Autism in the City of Surakarta. Methods: This type of research is a quantitative study with an observational analytic design through a cross sectional approach. This research will be conducted in the residency of Surakarta, in this study there is no intervention or treatment of respondents, and only observed once and do not follow up. Instrument, The instrument used to measure parenting style and playing patterns as well as children's social communication skills is a questionnaire. This questionnaire consists of three parts: the parenting style questionnaire aims to find out the form of parenting for children with autism. The play pattern questionnaire aims to find out the shape of the game patterns given to children with autism, and the social communication skills questionnaire aims to find out the social communication skills of children with autism. Results: Correlation statistical test using Spearmen`s rho analysis on parenting style variables with children's social communication skills obtained p value (sig.) 0.006, which means the value of p value 0.006 <0.05 means that there is a relationship between the form of parenting style h with communication skills social children, with a positive correlation with weak strength (r count 0.393); while variable on play patterns with social communication skills obtained p value 0.011 <0.05 means that there is a relationship between the form of play patterns with children's social communication skills, with a positive correlation direction and moderate strength (r count 0.363). Conclusion: Multivariate test results with multiple logistic regression showed that the R Square value of 0.057, which means that the parenting style variable and playing patterns can increase social communication skills of children with autism by 0.5% and the rest are explained in other factors outside the research model.